A high signal-to-background ratio H2S-specific fluorescent probe based on nucleophilic substitution and its bioimaging for generation H2S induced by Ca2+ in vivo. (December 2019) - Kang, Jin; Huo, Fangjun; Yao, Yishan; Yin, Caixia
Abstract: Hydrogen sulfide (H2 S), a new endothelium-derived relaxing factor ( EDRF ), which plays vital roles in regulating intracellular redoxstatus and other fundamental signaling processes involved in human health and disease. In this work, we designed a fluorescent probe for H2 S successive nucleophilic reaction with high signal-to-background (S/B) ratio. In the probe, we utilized 2-mercaptobenzoic acid as the distinguish reaction site and introduced 2, 4-dinitrophenyl to provide appropriate steric hindrance to realize specific response on well-structured H2 S. Other substances sulfur-containing do not disturb the detection of H2 S. The max emission with 197-fold enhancement exhibits high signal-to-background ratio. The detection limit was calculated to be 64 nM. Imaging assays in living cells showed that the probe could penetrate cells membrane easily and allowed to detect endogenous generation H2 S induced by Ca 2+ mediated cystathionine γ -lyase (CSE). Moreover, the probe was successfully used to detect exogenous H2 S in mice. Graphical abstract: A novel fluorescence H2 S probe based on nucleophilic substitution reactions, which with high signal-to-background ratios. This probe was successfully used to imaging ex-/endogenous H2 S in living cells, and exogenous H2 S in mice.Image 1 Highlights: This probe exhibit high signal-to-background ratio in response to H2 S. This probe was used to detect endogenous generation H2 S induced by Ca 2+ mediated cystathionine γ -lyase (CSE). This probe was successfully used to detect exogenous hydrogen sulfide in mice.